Respuesta :

Answer:

  • (f+g)(x) = 8x^3 + 5x^2 - 9

Step-by-step explanation:

Given

  • f(x) = 5x^2 -13 and g(x) =8x^3 +4

To find

  • (f+g)(x)

Solution

  • (f+g)(x) =
  • f(x) + g(x) =
  • 5x^2 -13 + 8x^3 +4 =
  • 8x^3 + 5x^2 - 9
MrPOOH

Given:

f(x) = 5x^2 - 13

g(x) = 8x^3 + 4

To Find:

The value of (f+g)(x) or f(x) + g(x) .

Explanation:

By putting the respected values, we get

f(x) + g(x) = 5x^2 - 13 + 8x^3 + 4

By simplifying the like terms, we get

f(x) + g(x) = 8x^3 + 5x^2 - 9

Answer:

(f+g)(x) = 8x^3 + 5x^2 - 9

ACCESS MORE